The Kirby-Xiao Intraoral Injection Technique: A Novel Method to Improve Perioral Cosmesis with Hyaluronic Acid Filler—A Review - Xiao, Anny (J Clin Aesthet Dermatol, 2020)
Perioral cosmesis is an important component of facial aesthetics. The perioral region is prone to revealing signs of aging due to repetitive movements and various environmental factors. While it is well established that perioral aesthetics can be effectively treated with hyaluronic acid dermal filler, there is limited published data available on injection techniques specifically designed for perioral rejuvenation. In this article, we review the perioral anatomy and current percutaneous filler injection techniques for perioral cosmesis. We then present a novel intraoral filler injection approach to improve perioral aesthetics with minimal downtime and high patient satisfaction.